Wearing weighted backpack dilates subjective visual duration: the role of functional linkage between weight experience and visual timing - Jia, Lina; Shi, Zhuanghua; Feng, Wenfeng (Frontiers in Psychology, 2015)
Bodily state plays a critical role in our perception. In the present study, we asked the question whether and how bodily experience of weights influences time perception. Participants judged durations of a picture (a backpack or a trolley bag) presented on the screen, while wearing different weight backpacks or without backpack. The results showed that the subjective dura-tion of the backpack picture was dilated when participants wore a medium weighted backpack relative to an empty backpack or without backpack, regardless of identity (e.g., color) of the visual backpack. However, the duration dilation was not manifested for the picture of trolley bag. These findings suggest that weight experience modulates visual duration estimation through the linkage between the wore backpack and to-be-estimated visual target. The con-gruent action affordance between the wore backpack and visual inputs plays a critical role in the functional linkage between inner experience and time perception. We interpreted our findings within the framework of embodied time perception.